Civilizational Akhlaq of Córdoba as a Model for Moral Revitalization among Indonesian Muslims - Muhammad Dakhlan Gazali; Syahrul Abdi Narotama; Wulan Afriza; Dimas Muhammad Hanief Arkaan; Kurnia Nur Khodijah; Dessy Asnita (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study analyzes the concept and implementation of akhlaq within the Islamic civilization of Córdoba as a model for revitalizing religious and moral values among contemporary Indonesian Muslims, aiming to identify Córdoba's ethical foundations, examine the factors driving moral degradation, and formulate an integrative revitalization strategy. Theoretical framework: This study is grounded in the concept of Civilizational Akhlaq, which extends the classical Islamic understanding of akhlaq beyond individual virtue to encompass its role as a foundational mechanism for civilizational development, integrating three interdependent dimensions: spiritual consciousness, intellectual excellence, and social responsibility. Literature review: Existing scholarship on akhlaq has predominantly focused on individual character formation, while research on Córdoba has concentrated on political history and scientific achievements. Studies on moral degradation in Indonesia have generally employed sociological approaches without integrating lessons from classical Islamic civilizations, revealing a gap that this study seeks to address. Method: This study employed a qualitative historical-comparative library research design. Data were collected through a systematic literature review using keyword searches across Scopus, Google Scholar, and other academic databases, selected through purposive sampling based on relevance and scholarly credibility. Data were analyzed using descriptive-analytical and thematic analysis techniques. Results: The findings reveal that Córdoba's civilizational success was built upon three interconnected pillars: spiritual, intellectual, and social dimensions forming an inclusive ethical system. Contemporary Indonesian Muslims face five major drivers of moral degradation, namely digital religious fragmentation, selective tolerance, religious literalism, moral privatization, and information overload. A revitalization framework consisting of epistemological reconstruction, institutional revitalization, technological integration, and cultural contextualization is proposed to address these challenges. Implications: The Civilizational Akhlaq framework has significant implications for educational institutions, religious organizations, and policymakers in Indonesia, providing a foundation for strengthening ethical leadership, social cohesion, and religious moderation within Indonesia's pluralistic society while enhancing global competitiveness through integration of spiritual values with technological innovation. Novelty: This study introduces Civilizational Akhlaq as a theoretical bridge between Islamic ethical thought and civilizational studies, demonstrating akhlaq's role as a civilizational force shaping institutions, governance systems, and intercultural relations, offering an integrative model connecting Córdoba's historical experience with contemporary moral challenges in Indonesia.